Development and optimisation of pre-treatment procedures to enhance total haemoglobin for carboxyhaemoglobin analysis in diluted blood samples - Dos Reis, Domonica-Jean (Department of Pathology, 2025)
Carbon monoxide (CO) is a toxic gas that is typically unnoticed due to its lack of colour, taste and odour. When CO is inhaled, it binds to haemoglobin in red blood cells and forms carboxyhaemoglobin (COHb). Used as a biomarker to investigate CO exposure, COHb can be determined in blood using a spectrophotometry-based technique called CO-oximetry. One of the challenges with certain CO-oximetric instruments is the requirement for total haemoglobin (tHb) to be above a specific concentration (1.61g/dL for the Radiometer ABL825 FLEX Blood Gas Analyser) for COHb determination in blood to be successful. Due to the nature of post-mortem forensic casework, sometimes the blood specimens sampled for COHb analysis are dilute, with tHb falling below the stated threshold. The purpose of this study was to assess and optimise two pre-treatment procedures to effectively increase tHb in excessively dilute blood samples, thereby enabling the determination of COHb using CO-oximetry. For the first procedure, ABL Radiometer AutoCheck5+ Level 2 quality controls and blank postmortem blood were spiked into diluted specimens to supplement the blood tHb. For the second procedure, a centrifugal evaporator (MiVac Quattro system) was used to concentrate the blood. The addition of the quality control and postmortem blank blood increased tHb in dilute specimens, however, no valid COHb results could be obtained. The application of evaporation on dilute samples increased tHb, and valid COHb results were obtained. The procedure showed at 30°C for 30 minutes requiring 500 μL, within-run and between-run imprecision values <5%, and bias within ± 20% for all samples. However, the results indicated a negative bias for all concentration levels, showing that the application of the procedure resulted in a slight (-5.9 to -15.0) underestimation of COHb. The stability of diluted samples, where water was added to blood, was also assessed, with the results showing instability (bias above the acceptable threshold of ± 20%) for the tested samples when stored at 4°C for one month. To test the application of the evaporation procedure, previous case samples that initially yielded no COHb results due to low tHb levels were processed using the validated procedure and analysed on the ABL825 FLEX Blood Gas Analyser. Of the 12 samples analysed, COHb results were successfully obtained for six, demonstrating the procedure's effectiveness in obtaining valid COHb results in samples with low tHb.